Avaliação clínica e por imagem do efeito do tratamento periodontal mecânico não cirúrgico associada à aplicação tópica de alendronato de sódio a 1% no reparo periodontal: ensaio clínico randomizado controlado - Bernardo de Carvalho Dutra (2014)
Alendronate Sodium is medically used in the treatment of osteoporosis and other bone diseases. In the past few years, studies have evaluated the effect of systemic use of Alendronate Sodium, especially in the treatment of structural bone defects caused by the evolution of periodontal inflammatory diseases. However, the prolonged and systemic use of Alendronate Sodium has been associated with the treatment of osteonecrosis of the maxilla. The objective of this randomized and controlled clinical trial was to evaluate the effect of non-surgical mechanical periodontal treatment, associated with the topical application of Alendronate Sodium at 1%, to individuals presenting cases of periodontitis. To the case, 16 individuals presenting chronic periodontitis were selected in the periodontal clinics of the Odontology department from the Pontifícia Universidade Católica de Minas Gerais, in the period of April of 2013 to May of 2014. A complete periodontal exam was performed three and six months after the base exam, registering the following clinical parameters: probing depth, measured insertion loss, bleeding on probing, plaque index. The evaluation of the bone defects was performed using the technics of subtraction radiography and cone beam computerized tomography in the base exam and six months after the non-surgical periodontal treatment. After the periodontal clinical exam, the individuals were submitted to the scaling and root planning procedures by quadrant. Subsequently, two sites presenting vertical, bilateral and interproximal bone defects were randomly selected for the applying of the Alendronate Sodium Gel at 1% (east side) or the Placebo Gel (control side). For comparing the clinical periodontal parameters and image exams, the Wilcoxon and McNemar tests were used when needed. To compare the results of subtracting the Fisher Exact test was performed. The results showed that non-surgical periodontal treatment associated with topical application of alendronate sodium 1% gel resulted in significant improvement in probing depth and increased filling of vertical bone defects when compared with the application of the placebo gel.